Designing and simulate proof of concept of storage architecture framework to resolve cifs netapp network attached storage (NAS) architectural design issue / Naqiuddin Abd Aziz - Abd Aziz, Naqiuddin (2012)
This project explains how storage works in the IT infrastructure environment. The researcher have analyze on the current IT infrastructure life cycle and storage architecture used in the organization. The researcher's main intention is to design anew storage architecture that can be utilized optimally to achieve the business need of the organization. In addition, the researcher has come out with Proof of Concept testing on how the new architecture works through experiment on the current live storage environment. The main objective was to Design Storage Architecture Framework with snapshot auto-delete policy to mitigate the risk of storage accessibility and reliability issue. And also to simulate the Proof-of-Concept of Storage Architecture designed through simulation and experiment of storage provisioned. This objective was achieve by applying IT Infrastructure Lifecycle Model to design new Storage Architecture Design and also through experimental analysis of storage simulation and experiment of provisioned storage. The researcher managed to achieve desired result of keeping the file system accessible with auto delete policy implementation, with some tolerance of backup snapshot being auto deleted. This research proves it significance on designing suitable IT architecture model on storage system for large enterprise , by maintaining storage accessibility with some tolerance on recoverability.